The Prevalence of Helicobacter pylori Infection Decreases with Older Age in Atrophic Gastritis - Shaohua Chen; Lixiong Ying; Mei Kong; Yu Zhang; Youming Li (Gastroenterology Research and Practice)
The clinical pathological characteristics of 3969 adult patients with chronic atrophic gastritis were retrospectively studied. The positivity of intestinal metaplasia and dysplasia in atrophic gastric specimens increased with age; however, H. pylori positivity and inflammatory activity decreased significantly with increased age. H. pylori infection was present in 21.01% of chronic atrophic gastritis patients, and 92.33% of the subjects with H. pylori infection were found to have simultaneous inflammatory activity. The intestinal metaplasia and dysplasia positivity markedly increased as the degree of gastric atrophy increased. In conclusion, the incidence of H. pylori infection decreased with age and correlated significantly with inflammatory activity in atrophic gastritis patients. The intestinal metaplasia and dysplasia positivity notably increased as the degree of gastric atrophy increased. Large population-based prospective studies are needed to better understand the progression of CAG.